Ongoing measures to enhance the efficiency of prescribing of proton pump inhibitors and statins in The Netherlands: influence and future implications. (November 2012) - Woerkom, Menno van; Piepenbrink, Hans; Godman, Brian; Metz, Joost de; Campbell, Stephen; Bennie, Marion; Eimers, Marietta; Gustafsson, Lars L
Background: Multiple reforms have recently been introduced in The Netherlands to improve prescribing efficiency. These include preference pricing policies for multiple sourced products, guidelines, and quality and efficiency targets, as well as regular pharmacotherapy meetings.Objectives: Assess the influence of these multiple measures on prescribing efficiency.Methods: Retrospective observational study of all reimbursed prescriptions for proton pump inhibitors and statins between 2000 and 2010 using the Genees-en hulpmiddelen Informatie Project (Health Insurance) database. Utilization measured in defined daily doses. Narrative review of reforms.Results: Reimbursed expenditure for the proton pump inhibitors fell by 58% in 2010 versus 2000 despite a threefold increase in utilization, helped by increasing utilization of generic omeprazole at only 2% of the prepatent loss price in 2010. Similarly, reimbursed expenditure for the statins fell by 14% in 2010 versus 2000 despite a 3.8-fold increase in utilization. Again, this was helped by increasing utilization of generic simvastatin at only 2% of the prepatent loss originator price.Conclusion: Multiple supply and demand measures, including the preference pricing policy, appear to have appreciably enhanced proton pump inhibitor and statin prescribing efficiency, providing examples to other countries.